Gambaran Komitmen Pernikahan pada Pasangan Suami Istri yang Menjalani Hubungan Pernikahan Jarak Jauh - Novita Budi Pramoni; Sri Ernawati; Dhian Riskiana Putri (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Long-distance marriages are increasingly common due to economic and work demands. This presents challenges in maintaining the commitment of married couples. This study aims to describe the nature of marriage commitment in long-distance relationships, examining it from personal, moral, and structural perspectives. Data collection techniques used in-depth interviews, observation, and documentation. The research informants were married couples in long-distance marriages. The results show that couples in long-distance marriages still have a strong commitment. The personal commitment aspect is reflected in the intensity of communication, maintained love and attraction, and is identified as a couple that is internalized in each other. The moral aspect shows from ethical awareness and cultural and religious values that strengthen responsibility towards partners. Meanwhile, structural commitment is identified through the presence of children, financial responsibility, and external obstacles that support maintaining the relationship. The psychological dynamics of couples are characterized by the ability to regulate emotions, cognitive adjustment to distance, and strong intrinsic motivation. These findings suggest that marital commitment can be maintained in long-distance marriages if supported by shared awareness, quality communication, and strong shared values.